Kerukunan dalam Komunikasi Antar Kelompok Agama Islam dan Hindu di Lombok - Wulan Purnama Sari; Sinta Paramita; Suzy Azeharie (BPSDMP Kominfo Manado, 2019)
It is not easy to reach a harmonious society in a multicultural country, the absence of good communication between stakeholders and groups that are related can create conflict. One of the key variables in fostering and realizing harmony is tolerance. The Lombok region which is the majority inhabited by Muslim communities can live in harmony and side by side with Hindu community. Based on the data obtained, Lombok is the city with the highest level of tolerance. This study examines how harmony can be created there and how the role of communication in creating harmony and communication between the two groups of different religions. This research was conducted with qualitative methods with a case study approach. Research data was obtained from interviews and observations. The results show that Hindu groups in Lombok live in the Lingsar region and in the area get along well because there are several factors, namely time, intermarriage, religion, and interaction. Communication also has a role in creating harmony because the basic condition of interaction is the existence of communication.Keywords : coordinated management of meaning